DRAMA AND DANCE PERFORMANCE OF THE USE OF LEARNING MEDIA OF CHARACTER EDUCATION OF ENVIRONMENT CARING (International Conference on Elementary Education, 2018)
The main issues in research is the an environmental crisis occurring in areas karawang assessed experiencing a number of environmental problems for industrial development and investment. This study attempts to find out the uses of performance art drama and dance as planting character education of caring environment in primary school student in karawang district. The research uses a qualitative approach by data collection method through observation , interview , and documentation. As for the result of research is the performance art drama and dance able to contribute to develop the character of caring environment. Proved of a scene how to care for environmental that can make to students to keep the environment and figures who played could give the awareness to students to take responsibility towards local environment. Hence this research recommended to educator to continue to innovate and improve their creativity in learning activities in particular planting character education caring environment.